Use of recycled construction and demolition waste (CDW) aggregates: A sustainable alternative for the pavement construction industry. (1st November 2016) - Ossa, A.; García, J.L.; Botero, E.
Abstract: Global production of construction and demolition waste has significantly increased over the last few decades, causing environmental problems due to its uncontrolled disposal. The use of recycled materials has been on the rise during the same period, primarily for the purpose of sustainable development and protecting the environment. The aim of this work is to study the use of recycled construction and demolition waste aggregates to create hot asphalt mixtures for urban paved roads, which can be an alternative to mitigate the environmental problems derived from the inadequate administration and disposal of this type of waste. For this purpose, several tests were performed to evaluate the susceptibility of asphalt concrete specimens to moisture damage and plastic deformation. Four different percentages (10–40) of recycled aggregates were used to create asphalt concrete specimens. The volumetric design of the asphalt mixes was based on the Superpave criteria. To accelerate the mix design process, the Ramcodes method, also known as the polygon of voids method, was used. The test results from this study indicate that the use of construction and demolition waste aggregates in percentages of up to 20% for paving urban roads is feasible. Highlights: We investigate the behavior of asphalt concrete elaborated with CDW aggregates. Susceptibilities to moisture damage and plastic deformation of asphalt concrete were assessed. Asphalt concrete specimens were elaborated with up to 40% of CDW aggregates. The incorporation of CDW aggregates in asphalt concrete for urban roads is a feasible option.